The Role of Education Policy in Improving Learning Quality: A Study of MGMP, Teacher Resilience and Academic Supervision in Gresik District Junior High Schools - Elly Nurdjanah; Budi Purwoko; Mufarrihul Hazin (Dinasti International Journal of Education Management And Social Science, 2025)
Education is the main foundation in shaping superior, faithful, pious and responsible human resources. Schools, especially junior high schools, have a strategic role in implementing the education process to face global challenges. However, the quality of education in Indonesia, including in junior high schools, still faces various complex challenges. This study aims to examine the role of education policy in supporting the implementation of subject teacher meetings (MGMP), increasing teacher resilience, and implementing academic supervision, as well as knowing the contribution of the three to improving the quality of learning in junior high schools in Gresik district. This research uses a qualitative approach with a library research method, by reviewing various literature sources such as journals, books, and previous research results. The results showed that the quality of learning in junior high schools in Gresik Regency increased through the synergy between MGMP, teacher resilience, and academic supervision. The three complement each other in building a collaborative and quality-oriented education ecosystem. MGMP supports teacher competence, resilience builds resilience, and supervision maintains learning quality.